EC175 complex integration considerations in zonal safety analysis - Vérité, N.; Bailly, S. (My University, 2014)
The EC175 is a new modern civilian helicopter which embeds complex and highly integrated functions. In this context, Airbus helicopters decided for this new development to implement a new process for zonal safety assessment activities. Mainly, this includes a dedicated safety team, specific organization and a general design recommendations guide.